THE ROLE OF SOCIAL MEDIA IN PROMOTING SPORTS FANATICISM - Alsulami, Mohammed (International Journal of Psychosocial Rehabilitation, 2020)
Social media is increasingly popular in Saudi Arabia, and most Saudis use it in many aspects of their life, business and career. Twitter is a social media platform that was created for users to share information and news, and users can be in different places around the world. In sports, the benefits of Twitter are enormous, and one of these is the sharing of information, such as activities, programs and news about sports teams. Sports broadcasters and fans get important information from Twitter. In fact through Twitter, careers of broadcasters, professionals, team players and fans are enhanced. Competition and rivalry have become intense among sports teams, fans and stakeholders.This research focused on the impact of Twitter on sports fanaticism. It assessed Twitter’s impact on sports, the many aspects of sports fans’ interaction, broadcasters’ live chat with fans, and the negative and positive impact of social media in Saudi life. Statistics reveal that in Saudi Arabia there are more than 25 million active social media accounts and more than 18 million active mobile social accounts. Traditionally, sports broadcasting was done through radio, television and newspaper. It is different in the age of information technology, where even the youngest of sports fans can access sports news through one’s mobile phone, iPhone, or iPad, and possibly interact with their favorite teams.This research project studied Twitter accounts of sports fans and focused on those accounts to determine the different perspectives of Twitter use and its impact. Some Twitter accounts of sports fans were analyzed, drawing from them the different perspectives of Twitter use and its impact. The theory in this research focused on uses and gratifications theory which was used to explain why people use Twitter and how Twitter impacts sports fanaticism in Saudi Arabia.